The functions f(x) and g(x) are defined below.
Which expression is equal to f(x) + g(x)?
![The functions fx and gx are defined below Which expression is equal to fx gx class=](https://us-static.z-dn.net/files/d30/66d3580b193900d4f35808768026a9fe.gif)
Answer:
To find the expression, we have to sum both functions.
We know that [tex]f(x) = \frac{x-16}{x^{2}+6x-40}[/tex] and [tex]g(x)=\frac{1}{x+10}[/tex]
So,
[tex]f(x) + g(x) = \frac{x-16}{x^{2}+6x-40}+\frac{1}{x+10}\\f(x)+g(x)=\frac{(x-16)(x+10)+(x^{2}+6x-40)}{(x^{2}+6x-40)(x+10)}\\f(x)+g(x)=\frac{(x-16)(x+10)+(x+10)(x-4)}{(x+10)(x-4)(x+10)}\\f(x)+g(x)=\frac{(x-16)+(x-4)}{(x-4)(x+10)}[/tex]
[tex]f(x) + g(x) = \frac{(x-16)+(x-4)}{(x-4)(x+10)}[/tex]